Estimation of Willingness to Pay for Development and Preservation of Liwa Botanical Garden Indonesia - Arista, Sundari Anda; Saptutyningsih, Endah (Journal of Economics Research and Social Sciences, 2020)
This research aims to find out how big the willingness of Kebun Raya Liwa visitors to pay for the ticket and to find the factors influencing that willingness. Visitors of Kebun Raya Liwa who are 20 years old or above are the subject of this report. This study uses primary data and uses a purposive sampling method to interview the subject with 304 people. The instrument used for the analysis is the Contingent Valuation Method (CVM). Each person is Rp 6.500 according to the average results of willingness to pay using Dichotomous Choice. Results of the analysis show that variables in age, education and income positively affect the willingness to pay. The perception of the visitors negatively affects the willingness to pay. While distance and frequency of visits do not affect the payment will.